Proptosis: A Rare Clinical Manifestation of Leukaemia in Children - Senali Y Seneviratne; Ejiroghene Ogonor; Majid Madni (International Journal of Medical and Pharmaceutical Case Reports, 2026)
Introduction: Leukaemia is the most common childhood malignancy worldwide, and acute myeloid leukaemia (AML) is the second most common type and carries a poorer prognosis than acute lymphoblastic leukaemia. Patients with AML may develop extramedullary lesions in the meninges, testicles, and orbits. We report the case of a child who presented with unilateral proptosis. Case Presentation: This case involved a 7-year-old girl, previously fit and well, whose parents initially noticed proptosis of her right eye. The proptosis gradually worsened, and she was brought to the Emergency Department. A CT scan of the head showed a right intra-orbital mass. Blood tests showed neutropenia, with blasts visible on the peripheral blood film. Flow cytometry confirmed a diagnosis of AML. She was transferred to the care of the Paediatric Oncology team and managed according to current guidelines. She has completed treatment and is currently in remission. Discussion: The differential diagnosis of unilateral proptosis in children is broad and includes pre-septal or orbital cellulitis, orbital haemangiomas, retinoblastoma, rhabdomyosarcoma, neuroblastoma, lymphangiomas, or thyroid eye disease. Orbital involvement can occur in childhood AML, and the presence of specific ocular lesions is associated with a higher risk of bone marrow relapse and central nervous system involvement, as well as reduced overall survival. Previous studies have shown that proptosis can indeed precede the manifestation of systemic symptoms of leukaemia. Conclusion: Unexplained proptosis in a child is a ‘red flag’ symptom, and it is important to maintain a high index of suspicion for leukaemia in these patients. Avoiding delays in diagnosis and treatment can improve overall outcomes for patients.